Education as weapon: poverty and school for Palestinian adolescent girls living in Israel. Issue 2 (17th February 2021) - Athamneh, Sinyal; Benjamin, Orly
ABSTRACT: The currently proposed meanings of paid work among adolescent girls who attend school neglect their negotiation of their belonging to their communities, calling for additional exploration of the field while focusing on belonging as achieved through respectability production. We investigate the meaning of adolescents' paid work by examining it in terms of prevalent paths of respectability production. Based on 20 interviews with adolescent Palestinian girls living in Israel whose families live in poverty and who are employed while attending school, we show that girls who live in a community that touts education as a 'weapon' and expects girls to aim high are in fact shamed by such an expectation. To restore their self-worth facing educational barriers, girls use paid work to enable three paths to respectability: parentification, market citizenship, and belonging. Our findings suggest that girls unable to produce respectability through education, turn to produce it through paid work.